An approach to the foreign officer profile in the Spanish army of the 18th Century: the early training of Lieutenant General Alejandro O’reilly (1723-1794) Una aproximación al modelo del oficial extranjero en el ejército borbónico: la etapa de formación del teniente general Alejandro O’reilly (1723-1794) - Óscar RECIO MORALES (Cuadernos Dieciochistas)
Irish-born Lieutenant General Alejandro O’Reilly (1723-1794) is one of the most controversial figures of Eighteenth-Century Spain. Already at the time he was branded as a mercenary, a parvenu and the king’s favourite. Historiography added to his name adjectives like Bloody O’Reilly or General Desastre. Over the years this reputation has not been accompanied by a better understanding of his figure. This contribution examines his early years of training, starting with his departure from Ireland in the early 1730s to enter the royal army with two of his brothers, until his return to Madrid in 1760 after participating as a military observer in Central Europe. These are unknown years, but they are essential to explain the different instruments that allowed O’Reilly to become the «king’s agent», such as his own merits, kinship, friendship, patronage, fellowship and professional endogamy. O’Reilly’s career allows us to approach a characteristic professional profile of Bourbon Spain, that is, the senior officers of foreign origin who occupied the highest military ranks and political positions in the 18th Century Spanish Empire. Alejandro O’Reilly (1723-1794) es una de las figuras más controvertidas del XVIII español. En su época fue tachado de mercenario, advenedizo y favorito del rey, y la historiografía unió su apellido a sonoros adjetivos como bloody O’Reilly o General Desastre. Con el paso de los años esta notoriedad no ha venido acompañada de un mejor conocimiento de su figura. Esta contribución examina sus primeros años de formación, desde su salida de Irlanda a principios de la década de 1730 para ingresar en los ejércitos reales, hasta su regreso a Madrid en 1760 tras su participación como observador militar en Centroeuropa. Esta etapa resulta fundamental para explicar los distintos instrumentos que permitieron a O’Reilly convertirse en «agente del rey», como sus méritos propios, el parentesco, la amistad, el clientelismo, el paisanaje y la endogamia profesional. Su carrera nos permite aproximarnos a un perfil característico de la España borbónica, el de los altos funcionarios de origen extranjero que ocuparon los grados más elevados del ejército y de la política al vértice de la Monarquía.